If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(t + 4) + -3(t + 5) = 13 Reorder the terms: 7(4 + t) + -3(t + 5) = 13 (4 * 7 + t * 7) + -3(t + 5) = 13 (28 + 7t) + -3(t + 5) = 13 Reorder the terms: 28 + 7t + -3(5 + t) = 13 28 + 7t + (5 * -3 + t * -3) = 13 28 + 7t + (-15 + -3t) = 13 Reorder the terms: 28 + -15 + 7t + -3t = 13 Combine like terms: 28 + -15 = 13 13 + 7t + -3t = 13 Combine like terms: 7t + -3t = 4t 13 + 4t = 13 Add '-13' to each side of the equation. 13 + -13 + 4t = 13 + -13 Combine like terms: 13 + -13 = 0 0 + 4t = 13 + -13 4t = 13 + -13 Combine like terms: 13 + -13 = 0 4t = 0 Solving 4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '4'. t = 0 Simplifying t = 0
| -50(b-5)=-1000 | | 7x-7(x-7)=24x+5 | | (4x+4)=(74-x) | | y=-3.5x^2+210x | | 2.5x+16=-4 | | 7x-(7)=24+5x | | -50(b-5)=500 | | 8y-3=179-2y | | 2(x-4)-(6+x)=3x-4 | | ln(2-x)=0.5 | | =2(5g^2-14g+8) | | 7p+6=17 | | 4t+23=11t-2 | | 9=3/4(-12x+36) | | 6x+8y=4.1 | | 2k=7k+15 | | z+50=z+10+4z | | 3x-4(5x+7)=-130 | | 95+75x=96 | | u=(-(-2.42)±√(〖(-2.42)〗^2-4(1)(-102.64)))/(2(1)) | | y=8E-05x+0.0002 | | 99+v=5300/10 | | -20(20+-x)=100 | | -21-18=-3 | | 1/2(4x-16)=2(2x-8) | | -20(20+-x)=200 | | 5x+3y(2x)=22 | | 6m+2n+9m+8n= | | 21-18=-3 | | -20(20+-x)=800 | | x-4=40 | | 38s-10=0 |